Design of QPSK demodulator / Hasbullah Hussein - Hussein, Hasbullah (1995)
This paper describes the design, construction and testing of a quadrature phase shift keying (QPSK) demodulator. QPSK is an efficient modulation scheme.This scheme is used extensively in communication systems e.g digital satellite, digital microwave and also in the newly introduced digital cellular communication. The purpose of the QPSK demodulator is to demodulate me modulated carrier signal and transform it to the original data or information. The input signal of the receiver is obtained from the QPSK modulator. The QPSK modem (modulator /demodulator) will be operating at frequency of 10 MHz and input data rate of 2.4 kbps.